Marvel commercially-authored universe - Garrido Parrilla, Joaquín David; Horno López, Antonio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The film medium has undergone different technological developments that have allowed it to meet the expectations of the demanding spectator. In addition, there have been many cinematographic movements that have led the specialised critics to catalogue the different filmmakers. The dividing line between authorship and commerciality is becoming increasingly blurred. The science fiction genre has positioned itself as the most attractive genre in today's contemporary society. In this context, this research paper proposes an analysis of essential aspects of the Marvel Cinematic Universe that blurs the aforementioned line through a new identity of commercial authorship.